Science Education for Sustainable Development: A Theoretical Framework - Sharma, Mudita; Mishra, Jyoti (SCHOOL SCIENCE, 2017)
Sustainable development is an emerging need of present times. Sustainable development is the development that meets the needs of present without compromising the ability of future generations to meet their own needs. Man is always curious about the world surrounding him and science helps in this domain of knowledge. Science is a dynamic body of knowledge which involves many interconnected steps to solve any problem. Science is knowledge and knowledge is power; power is essential for sustainable development, so science education and sustainable development are interrelated with each other. Science helps people to acquire values, skills and knowledge necessary to build sustainable development. We can say that education for sustainable development is to renew education, teaching and learning and it also provides comfortable life to us. Science education can develop positive attitude towards science as a major factor in the society which leads to the path of sustainable development. For sustainable development there should be a balance between science and humanity, ecology, economy and prosperity and peace. This paper is intended to stimulate discussion about science education and its role in sustainable development. It also elaborates the science education in relation with sustainable development which helps to achieve the Millennium Development Goals (MDGs). It also discusses the challenges for sustainable development.